Students' Perception in Implementing Google Meet and Video Call' s App on Arabic Speaking Class - Halimatus Sa`diyah; Dian Arsitades Wiranegara (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
The development of technology and the dynamics of virtual and non-virtual learning as a form of mixed learning also occurs in the practice of learning to speak Arabic. However, not all media can support learning. Thus, this study aims to determine the perception of PKPBA students of the Psychology Faculty of UIN Maulana Malik Ibrahim Malang in Ps.2 class on the use of google meet and video calls in the practice of speaking Arabic. This type of research is descriptive and qualitative. The data was obtained from questionnaires via google form 35 research subjects, namely PKPBA students of the Psychology Faculty of UIN Maulana Malik Ibrahim Malang class Ps.2 who have studied Arabic speaking skills in the first semester of the 2021/2022 academic year. The data is processed using a Likert scale and is equipped with tables and pie charts. The result showed that (1) the use of video calls was easily accessible from google meet, (2) the use of video calls was easier to use during practice and get corrections from friends and lecturers than on google meet, and (3) video calls were more effectively used in the practice of speaking with a total number of a limited number of students while google meet is effectively used in the practice of group speaking in large groups/one class in a longer duration of time.